Managing pollination in apple for higher yield - Srivastava, K K; Sharma, O C; Singh, S R; Ahmed, N (Indian Horticulture, 2019)
Most of apple varieties are self-unfruitful and they cannot produce fruit by their own pollen, hence require some compatible cultivars. Red delicious and their strains are chief cultivar abundantly cultivated in Jammu and Kashmir. This cultivar is self-unfruitful, produces good crops only after cross-pollination. The peculiar flower structure of Delicious strains is another reason of poor fruit setting. As flowers are arranged in an upright position, honey bees are able to push their proboscises into the rectory from side without rubbing over the stigma at top of flowers, thus no pollen put over the stigma, resulting in poor yield. Insufficient pollen loads led poor fertilization, uneven fruit or seed development, non-symmmetrical fruit growth, high fruit drop and crop took long period to mature.